Analisis Hambatan Dalam Manajemen Kelas di SD Negeri 045965 Peceren Dan Strategi Mengatasinya - Yosefo Gule; Dira Vandora br Barus; Maria Yanuaria Sihombing; Rojuwita Munthe; Agnes Monika Sembiring (Genta Bangsa : Jurnal Ilmu Pendidikan, 2026)
Classroom management is an essential competency that elementary school teachers must master to create a conducive and effective learning atmosphere. This study aims to analyze the obstacles faced by teachers in classroom management at SD Negeri 045965 Peceren, Berastagi District, Karo Regency, and to formulate relevant strategies to overcome them. The study employed a descriptive qualitative method through direct observation, teacher interviews, and field documentation conducted on 22 May 2026. The results show that the classroom management obstacles identified include undisciplined student behavior, limited facilities and instructional media, heterogeneous academic ability among students, minimal parental support, and limited teacher competence in applying proactive classroom management techniques. These factors are interrelated and stem from student, teacher, physical environment, family, and school supervision aspects. Recommended strategies include participatory classroom rule-setting, a consistent reward-and-consequence system, differentiated instruction, improved school-parent communication, and strengthening teacher competence through continuous training and supervision. The study concludes that successful classroom management requires synergy among teachers, principals, parents, and the entire school community.